An Indoor Navigation Solution for Visually Impaired People - Faria, João Vitor de; Frinhani, Rafael de Magalhães Dias; Carvalho, Luiz Olmes (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2025)
This article describes the development of a mobile application designed to assist the navigation of visually impaired individuals in indoor environments. The application interacts with Bluetooth devices called beacons, which help identify the trajectory. The beacons’ arrangement and the environment’s computational modeling were carried out using techniques such as trapezoidal decomposition and graph representation. The application uses threads to identify the shortest paths between source and destination beacons. It also provides audio instructions about the locations the user must pass through to reach the destination, correcting routes if the user is heading in the wrong direction or location. We validated the solution in a real-world environment and proved capable of successfully guiding the user within the studied environment.